Diagnostic accuracy of the Pain (P), Enjoyment (E), and General activity (G) scale, a three-item questionnaire, for grading the impact of orofacial pain-related dysfunction - Roldán-Majewski, Carolina; Broedel, Elias; von Korff, Michael; Rammelsberg, Peter; Schindler, Hans J.; Giannakopoulos, Nikolaos Nikitas (Pain, 2022)
Purpose of this study was to examine the discriminative properties of the 3-item Pain (P), Enjoyment (E), and General activity (G) (PEG) questionnaire for grading impact of nondental orofacial pain. Two hundred eighty-six consecutive patients with orofacial pain of nondental origin filled out the PEG questionnaire and Graded Chronic Pain Scale (GCPS, version 2), Correlation between the PEG and GCPS scores, internal consistency of the PEG, and differences between groups were examined statistically (level of significance: P <= 0.05). The mean (+/- SD) age of the 213 patients (158 female) who were included in the analysis was 43.1 (+/- 16.7) years. Of the sample, 48.8% (n = 104) had some degree of orofacial pain-related disability (mean overall characteristic pain intensity: 51.2 +/- 23.2, average overall PEG score: 4.3 +/- 2.7, and average PHQ-9 score: 8.2 +/- 6.5). No significant differences were found between the sexes for any score. The number of disability points (GCPS) and overall PEG score showed a strong and positive correlation (Spearman rho = 0.77, P < 0.001). The internal consistency of the PEG questionnaire was high (Cronbach alpha = 0.86). Assuming 3 different levels of orofacial pain-related disability (mild, moderate, and severe), we obtained overall accuracy of 69.01%, with high specificity for mild and severe cases. The 3 PEG groups (mild, moderate, or severe) differed from each other significantly regarding their clinical grading according to the GCPS (Kruskal-Wallis, P < 0.001). Analysis of the receiver operating characteristic curve showed that a single cutoff value of 3.8 points in the PEG score yields adequate validity (sensitivity = 0.91 and specificity = 0.78). The proposed 2 cutoff points (upper = 7 and lower = 4) yield low sensitivity for the upper threshold. The 3-item PEG questionnaire is suitable for grading impact of nondental orofacial pain.
Gesehen am 13.12.2022